2022
DOI: 10.1128/spectrum.02411-22
|View full text |Cite
|
Sign up to set email alerts
|

Two Hybrid Histidine Kinases Involved in the Ethylene Regulation of the Mycelial Growth and Postharvest Fruiting Body Maturation and Senescence of Agaricus bisporus

Abstract: Ethylene regulates diverse physiological activities in bacteria, cyanobacteria, fungi, and plants, but how to perceive ethylene by fungi only remains unknown. In this study, we identify two biologically functional ethylene receptors in the basidiomycete fungus Agaricus bisporus , which fills the gaps of deficient fungal ethylene receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Briefly: a 5.5 mL headspace vial contained a 1.8 mL mixture composed of 150 mM NaHCO 3 , 30 mM ascorbic acid, 1.0 mM ACC, 0.1 mM FeSO 4 , and 0.1 mg enzyme protein in 100 mM Tris-HCl buffer at pH 7.2. After shaking incubation at 30 °C for 1 h, 1 mL gas was withdrawn for ethylene determination by gas chromatography (GC-2010 plus, Shimadzu, Kyoto, Japan) [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Briefly: a 5.5 mL headspace vial contained a 1.8 mL mixture composed of 150 mM NaHCO 3 , 30 mM ascorbic acid, 1.0 mM ACC, 0.1 mM FeSO 4 , and 0.1 mg enzyme protein in 100 mM Tris-HCl buffer at pH 7.2. After shaking incubation at 30 °C for 1 h, 1 mL gas was withdrawn for ethylene determination by gas chromatography (GC-2010 plus, Shimadzu, Kyoto, Japan) [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Western blotting results showed that LeHOG1 phosphorylation and LeATG8 protein levels followed the same trend. Now, ROS and the autophagy mechanism and their functions in relation to mushroom growth and fruit-body formation are becoming hot research topics [ 10 , 35 , 36 ]. Thus, the correlation between ROS and autophagy in L. edodes , as well as the role of LeHOG1 protein in ROS-mediated oxidative stress, require further study.…”
Section: Discussionmentioning
confidence: 99%
“…In Cordyceps militaris , the best reference genes for inducing fruiting bodies in wheat medium and pupae are gpd / rpb1 and rpb1 / try , respectively [ 32 ]. However, during the fruiting bodies development of Flammulina velutipes , Botrytis cinerea and Agaricus bisporus , the stable reference genes are gapdh , tubulin and EF1-α , respectively [ 33 35 ]. In the research related to the development of O .…”
Section: Discussionmentioning
confidence: 99%